Whole-body vibration and postural stress among operators of construction equipment: A literature review - N. Kumar Kittusamy (The National Institute for Occupational Safety and Health (NIOSH), 2004)
Operators of construction equipment perform various duties at work that expose them to a variety of risk factors that may lead to health problems. A few of the health hazards among operators of construction equipment are: (a) whole-body vibration, (b) awkward postural requirements (including static sitting), (c) dust, (d) noise, (e) temperature extremes, and (f) shift work. It has been suggested that operating engineers (OEs) are exposed to two important risk factors for the development of musculoskeletal disorders: whole-body vibration and non-neutral body postures. Method: This review evaluates selected papers that have studied exposure to whole-body vibration and awkward posture among operators of mobile equipment. There have been only few studies that have specifically examined exposure of these risk factors among operators of construction equipment. Thus other studies from related industry and equipment were reviewed as applicable. Conclusion: In order to better understand whole-body vibration and postural stress among OEs, it is recommended that future studies are needed in evaluating these risk factors among OEs.